Urgensi Sertifikat Laik Fungsi (Slf) Bangunan Terhadap Usaha Jasa Akomodasi Pariwisata di Kota Denpasar - I Nyoman Gede Sugiartha; I Gusti Agung Ayu Gita Pritayanti Dinar; I Made Aditya Mantara Putra (Kertha Wicaksana, 2021)
The application of the Online Single Submission (â€œOSSâ€) is implemented by the government in order to streamline the business licensing process which has been considered very inefficient and requires a lot of time and money, requiring all Limited Liability Companies (â€œPTâ€) established under the laws of the Republic of Indonesia to obtain a Business Identification Number. (â€œNIBâ€) and further adjust the permits previously obtained by each of the PT, both those related to operations and non-operations, with the permits issued by OSS. As a result of the implementation of the OSS, companies that have applied for and obtained a Business Permit (Target Business Registration Certificate) but have not yet become effective, must fulfill other commitments, one of which is the Certificate of Feasibility of Function (â€œSLFâ€). The formulation of the problem in this study: (i) Application of the arrangement of the Function Feasibility Certificate (SLF) for buildings in the Province of Bali, (ii) the urgency of the implementation of the Commitment to the Certificate of Feasibility of Function (SLF) in the Province of Bali. This research uses normative legal research methods, with a statutory approach and legal concept analysis. The theory used in examining the problems in this research is the theory of economic law, the theory of state sovereignty and the conception of law as a policy process. Through this research, it can be determined the urgency of implementing the commitment to the Certificate of Functional Worth (SLF) for buildings in Denpasar City. Consistency of professional application based on justice, certainty and legal benefits by the government is needed so as to create economic growth through ideal and sustainable tourism in Bali. The benchmark for implementing the SLF commitment is by taking into account various legal factors and the efficiency of government policies in a deep, structured and systematic manner.